The Performance of an Ultrasound Flotation System for Heavy Metal Removal from Acid Mine Drainage in Wheal Jane Mine - Wan Faizal, Wan Ishak (2008)

(untitled)
The aim of this study is to compare the effect of the ultrasound on the removal of heavy metals (Iron, Zinc and Copper) from Acid Mine Drainage (AMD) using a Denver Cell flotation. Samples from the Wheal Jane mine site, Cornwall, which contain high loadings (32 ppm of iron, ppm zinc) of heavy metals, were chosen for this study. Synthetic AMD and individual metal solutions are used in the initial experiments to optimise the flotation process condition prior to using real AMD. Initial flotation results with column and Denver flotation units were compared before ultrasound was added to the process flow sheet. The Denver flotation unit gave better metal removal compared to the traditional column flotation unit and successfully removed the metals (optimum removal 100% copper, 99% iron and 96% zinc) and hence was selected for the ultrasound test programme. Three different process methods, ultrasound treatment followed by Denver flotation cell, Denver flotation cell alone and ultrasonic applied simultaneously with Denver flotation cell were tested for every sample. Ultrasound pre-treatment enhances the metal removal when coupled with the flotation system. In the early stages of the treatment (first 2 minutes of flotation time), up to a 10% increase in metal removal (iron, zinc) compared to the Denver cell alone was achieved by using ultrasound treatment. This could prove to be a significant improvement in removal efficiency at the early stages of separation. The correct pH for the metal to precipitate and the optimum dosage of suitable frother however are also major contributors to the success of this technique.